2002
DOI: 10.1620/tjem.197.119
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Antioxidant Enzymes in Turkish Population: Relation to Age, Gender, Exercise, and Smoking.

Abstract: The purpose of this study was to examine the change in lipid peroxidation and antioxidant enzyme activities in healthy subjects and to evaluate the concentrations of superoxide dismutase, glutathione peroxidase and malondialdehyde, an end product of lipid peroxidation in exercise and smoking. Study included 257 appearently healthy individuals, 133 males and 124 females. In all subjects, malondialdehyde (MDA) levels were analyzed as an indicator of the lipid peroxidation activities. Superoxide dismutase, glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
26
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 13 publications
10
26
3
2
Order By: Relevance
“…This could be attributed to the initiation and promotion of multistage carcinogenesis induced by free radicals which were increased in oral cancer [11]. Free radicals and radical mediated lipid peroxidation reaction can alter according to sex, as per the study by Bast et al, [21], but in our study, these were not much variations in sex, which was similar to the study by Bulent et al, [22].…”
Section: Discussionsupporting
confidence: 89%
“…This could be attributed to the initiation and promotion of multistage carcinogenesis induced by free radicals which were increased in oral cancer [11]. Free radicals and radical mediated lipid peroxidation reaction can alter according to sex, as per the study by Bast et al, [21], but in our study, these were not much variations in sex, which was similar to the study by Bulent et al, [22].…”
Section: Discussionsupporting
confidence: 89%
“…MDA is one of the most often used biomarkers of oxidative stress on lipids associated with aging. An age-related increase in the plasma concentration of MDA has been documented in several studies [28,33,35,36]. Miguel J et al, in their study on a group of healthy men and women ranging in age from 20 to 70 years, demonstrated an age-related increase in MDA levels only among the women [28].…”
Section: Discussionmentioning
confidence: 88%
“…Although study populations in these studies were older and their mean age was comparable to our study (around 60 years of age), it is not possible to compare AOPP levels from our study with other reports in the literature since only 25-36% of the cases were women. Further studies comparing AOPP levels between men and postmenopausal women of the same age groups, with or without coronary artery diseases, are needed to clarify the effect of age and gender on AOPP levels, as well as to detect critical cut-off levels to predict coronary artery disease in postmenopausal women [33]. Reports in the literature suggest that protein oxidation occurs in the plasma of coronary artery disease as well as uremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate a persistent oxidative stress that might be associated with intravascular inflammation in patients during convalescence and release from hospital. myocardial infarction; percutaneous coronary intervention; inflammation; soluble intercellular adhesion molecule-1; lipid peroxidation © 2006 Tohoku University Medical Press While oxidative stress has been shown to be related with the age and living habits (Ozbay and Dulker 2002), it plays an important role in the development of vascular diseases that affect vital organs, in particular brain and heart (Zarkovic 2003;Zarkovic et al 2004;Madamanchi et al …”
mentioning
confidence: 99%